National Images as Integrated Schemas: Subliminal Primes of Image Attributes Shape Foreign Policy Preferences. Issue 3 (31st March 2015) - Castano, Emanuele; Bonacossa, Alain; Gries, Peter
Abstract : International Image Theory (IIT) suggests that individuals maintain holistic images of other countries that are akin to schemas, or stereotypes, and that these national images shape both attitudes and foreign policy preferences. Previous research has manipulated national images via explicit descriptions of fictitious countries and found initial evidence for such effects. Here we extend this research and investigate whether (1) priming subliminal associations of a real country with image‐specific adjectives leads individuals to endorse such an image for that country, and whether (2) the endorsement of national images mediates observed effects on foreign policy preferences. We first demonstrate that the perception of a nation's power can be experimentally manipulated via associative implicit priming (pilot study). In Experiment 1, we then found that participants who were subliminally primed with adjectives pertinent to the ally, enemy, or dependent image of a country evaluated the country on the National Image scale (Alexander, Brewer, & Hermann, 1999) in a manner consistent with the prime. Experiment 2 further showed that induced national images mediate priming effects on foreign policy preferences.